The national approach to de-radicalisation of Daesh in Malaysia - Ismayatim, Muhammad Asyraf; Omar, Muhamad Fuzi (IIUM Press, 2017)
This book looks at the factors of radicalisation of Malaysian citizens who have been influenced by Daesh’s propaganda and ideology. Apart from that, this book also examine the manifestation of radicalisation by the people who have been radicalised and joined Daesh. Another part of this book is about the way Malaysian government responds to the threat of radicalisation especially among its citizens, particularly when it comes to the radical threat posed by Daesh militant groups and its affiliates. Sources taken for this book are both the interviews and literatures, as well as open sources. The findings indicate that there are four main factors of radicalisation which are external factors, internal factors, ideological factors and personal factors. Apart from that, the manifestation of radicalization is also identified as cognitive manifestation and behavioural manifestation. Other than that, the measures taken by the Malaysian government in response to this issue are implemented within four scopes which are the legislative approach, rehabilitative approach, counter-violence programme and international cooperation.